Age at Onset of Menarche and Puberty of Girls in Aydin Region and the Factors Affecting Them - Ebru Ataş Aslan; Tolga Ünüvar (Trends in Pediatrics, 2021)
Objective: In this study, we aimed to determine the range of mean age at onset of menarche (AOM) and puberty (AOP) of girls living in Aydin province and to determine the factors affecting the onset age of menarche.